Excitation functions of deuteron-induced nuclear reactions on erbium in the energy range of 4–24 MeV - Khandaker, Mayeen Uddin *; Haba, H.; Komori, Y.; Otuka, N. (Elsevier, 2020)
Excitation functions for the natEr(d,x)163,165,166,167,168,170Tm and natEr(d,x)171Er nuclear reactions were measured from the respective thresholds up to 24 MeV by using a stacked-foil activation technique combined with HPGe γ-ray spectrometry. Measured data show a partial agreement when compared with the available literature data, theoretical data extracted from the TENDL-2019 library, and predicted data by the model code EMPIRE-3.2.2. Estimated physical thick target yields of the reaction products show close values to the directly measured ones available in the literature. The deduced yield curves indicate that a typical irradiation (Ed = 15 MeV, Id = 100 µA, tirr = 72 h) of enriched 167Er target by a low energy deuteron cyclotron is suitable to obtain more than a hundred GBq activity of 167Tm with negligible impurity from 168Tm. Measured data of 170Er(d,p)171Er reaction have great significance to improve the predicting capability of the model code.